ChemInform Abstract: Efficient Room‐Temperature Synthesis and Antimicrobial Study of Novel 2‐Aroylbenzofuran‐3‐ols from Substituted Methyl Salicylates and Phenacyl Bromides. Issue 24 (2nd June 2014) - Kulkarni, Rashmi S.; Hanumanthappa, Suresha Kumara T.; Gopalpur, Nagendrappa; Vijaya Kumar, Sowmya H. B.; More, Sunil S.
Abstract Some of the new 2‐aroylbenzofuranols (III) (21 examples) show prominent antibacterial and/or antifungal activities.